2014
DOI: 10.19030/iber.v13i4.8686
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Learning Orientation And Business Performance And The Moderating Effect Of Competitive Advantage: An Accounting Services Firms Perspective

Abstract: This study examines the influence of learning orientation on business performance (achievement of sales and profit objectives) in the context of pure service, specifically that of public accounting services firms. The conceptual framework used in this research has been drawn from marketing, finance, and organizational behavior theory. Specifically, relationships related to learning orientation, sources of competitive advantage, and business performance have been identified.This research tests a framework about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
3
9
0
1
Order By: Relevance
“…In order to achieve and maintain competitive advantage in a rapidly changing business environment, organizations must be able to improve their learning capacity (Marquardt, 1996). This result is in line with Ismail et al’s (2013) research and Martinette et al’s research (2014), stating that organizational ability in learning is critical in achieving competitive advantage and a positive relationship between learning orientation and competitive advantage. Mahmood and Hanafi (2013) emphasized the learning orientation and sources of competitive advantage as the key factors of SME success.…”
Section: Conclusion and Managerial Implicationsupporting
confidence: 90%
See 1 more Smart Citation
“…In order to achieve and maintain competitive advantage in a rapidly changing business environment, organizations must be able to improve their learning capacity (Marquardt, 1996). This result is in line with Ismail et al’s (2013) research and Martinette et al’s research (2014), stating that organizational ability in learning is critical in achieving competitive advantage and a positive relationship between learning orientation and competitive advantage. Mahmood and Hanafi (2013) emphasized the learning orientation and sources of competitive advantage as the key factors of SME success.…”
Section: Conclusion and Managerial Implicationsupporting
confidence: 90%
“…Martinette et.al. (2014) described a positive relationship between learning orientation and company’s performance and learning orientation and competitive advantage. Mahmood and Hanafi (2013) described the positive and significant influence of learning orientation towards competitive advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the studies of MO towards firm performance indicate the positive relationship (Lee et al, 2015;Qu & Zhang, 2015), whereas Arshad et al (2012) demonstrate MO had a negative impact on firm performance. Similarly, the studies proved positive relationship between LO and firm performance (Frank et al, 2012;Martinette et al, 2014), while Long (2013) found that LO has no significant effect on firm performance. Additionally, access to finance has a strong positive impact on firm performance (Nwosu & Orji, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…Without a shared vision, organizational members are less likely to know what organizational expectations exist (Sinkula et al, 1997). Additionally, some studies have been conducted on the contribution of LO to firm performance and found that LO has a significant on performance (Martinette & Obenchain-Leeson, 2012;Martinette et al, 2014;Frank et al, 2012). In contrast, several studies report that LO has a non-significant influence on performance (Wolff et al, 2015;Suliyanto & Rahab, 2012;Ma et al, 2011).…”
Section: Learning Orientationmentioning
confidence: 99%
“…Los resultados de la relación AO-DO sugieren que tanto los socios, dueños y/o altos mandos de la empresa que buscan obtener mejores resultados organizacionales deberían utilizar el aprendizaje dentro de la organización, es importante se fomente en la empresa un clima de cultura organizacional que detone el AO y de esta manera obtener mejores resultados organizacionales. Los hallazgos concuerdan con los de (Martinette & Obenchain-Leeson, 2014;Cardona & Calderón, 2006;Dulger, Alpay, Yilmaz, & Bodur, 2014;Araiza et al, 2014;García, Jiménez, & Lloréns, 2011;Gálvez et al, 2013;Abbade, 2012;Martínez , Vega, & Vega, 2016;Sikora et al, 2016;Homaid, Minai, & Al-Ansi, 2018), en cuanto a que se confirma la influencia positiva de la relación AO-DO, sin embargo se enfatizan los hallazgos en confirmar esta relación en las pymes, como una contribución que abona a la necesidad de estudios empíricos sobre el tema.…”
Section: Conclusionesunclassified